Phenotypic and functional characteristics of CD39high human regulatory B cells (Breg). (1st February 2016) - Figueiró, F.; Muller, L.; Funk, S.; Jackson, E.K.; Battastini, A.M.O.; Whiteside, T.L.
ABSTRACT: CD39 and CD73 are key enzymes in the adenosine (ADO) pathway. ADO modulates pathophysiological responses of immune cells, including B cells. It has recently emerged that a subpopulation of ADO-producing CD39 + CD73 + B cells has regulatory properties. Here, we define the CD39 high subset of these cells as the major contributor to the regulatory network operated by human B lymphocytes. Peripheral blood B cells were sorted into CD39 neg, CD39 inter and CD39 high subsets. The phenotype, proliferation and IL-10 secretion by these B cells were studied by flow cytometry. 5′-AMP and ADO levels were measured by mass spectrometry. Agonists or antagonists of A1 R, A2A R and A3 R were used to study ADO-receptor signaling in B cells. Inhibition of effector T-cell (Teff) activation/proliferation by B cells was assessed in co-cultures. Cytokine production was measured by Luminex. Upon in vitro activation and culture of B cells, the subset of CD39 high B cells increased in frequency ( p < 0.001). CD39 high B cells upregulated CD73 expression, proliferated (approximately 40% of CD39 high B cells were Ki-67 + and secreted fold-2 higher IL-10 and ADO levels than CD39 neg or CD39 inter B cells. CD39 high B cells co-cultured with autologous Teff suppressed T-cell activation/proliferation and secreted elevated levels of IL-6 and IL-10. The A1 R and A2A R agonists promoted expansion and functions of CD39 high B cells. CD39 ectonucleotidase is upregulated in a subset of in vitro -activated B cells which utilize ADO and IL-10 to suppress Teff functions. Proliferation and functions of these CD39 high B cells are regulated by A1 R- and A2A R-mediated autocrine signaling.